Application of PCR-based serogrouping of selected Salmonella serotypes in Malaysia - Bee Kim Lim; Kwai Lin Thong (Journal of Infection in Developing Countries)
Background: Differentiation of Salmonella enterica into its serogroups is important for epidemiological study. The objective of the study was to apply a multiplex PCR targeting serogroups A, B, C1, D, E and Vi-positive strains of Salmonella enterica commonly found in Malaysia. A separate H-typing multiplex PCR which identified flagellar antigen “a”, “b” or “d” was also optimized to confirm clinical serotypes, S. Paratyphi A and S. Typhi. Methodology: Sixty-seven laboratory Salmonella enterica strains were tested. Six sets of primers targeting defined regions of the O antigen synthesis genes (rfb gene cluster) and Vi antigen gene (viaB) were selected and combined into a multiplex PCR for O-grouping. Four primers (H-for, Ha-rev, Hb-rev and Hd-rev) were used in the second step multiplex PCR for H-typing. The optimized mPCR assays were further evaluated with 58 blind-coded Salmonella strains. Results: The multiplex PCR results obtained showed 100% concordance to the conventionally typed serogroups. Validation with 58 blind coded Salmonella strains yield 100% accuracy and specificity. Conclusion: Based on this study, PCR serogrouping proved to be a rapid, alternative method for further differentiation of Salmonella enterica.